2016
DOI: 10.1371/journal.pone.0166959
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Diversity of Culex pipiens Biotypes and Hybrids in Farm, Peri-Urban, and Wetland Habitats in Europe

Abstract: Despite the presence of Culex (Cx.) pipiens mosquitoes and circulation of West Nile virus (WNV), WNV outbreaks have so far not occurred in northern Europe. The species Cx. pipiens consists of two morphologically identical biotypes, pipiens and molestus, which can form hybrids. Until now, population dynamic studies of Cx. pipiens have not differentiated between biotypes and hybrids at the European scale, nor have they used comparative surveillance approaches. We therefore aimed to elucidate the relative abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 38 publications
1
36
3
1
Order By: Relevance
“…pipiens f molestus while none of the specimens collected in traps were bioform molestus. Contrasting with the results from (Vogels, Möhlmann et al 2016) where they found the Cx. pipiens f molestus in rural sites and hybrids in an urban site where no nuisance problems have been reported.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…pipiens f molestus while none of the specimens collected in traps were bioform molestus. Contrasting with the results from (Vogels, Möhlmann et al 2016) where they found the Cx. pipiens f molestus in rural sites and hybrids in an urban site where no nuisance problems have been reported.…”
Section: Discussioncontrasting
confidence: 91%
“…In northern Europe, Cx. pipiens bioforms have been thought to be more isolated from each other and hybrids are less common , Vogels, van de Peppel et al 2015, Vogels, Möhlmann et al 2016. Compared to the few previous reports of Culex pipiens f molestus in Sweden we have found specimens in several rural areas where we would not have expected it to be present.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The biotype composition of the mosquito population, which has been shown to be highly variable across different locations in Europe 31, 32 . To express the variability we selected three representative biotype compositions; either dominated by pipiens ( m p  = 0.8, m m  = 0.1, and m h  = 0.1), dominated by molestus ( m p  = 0.1, m m  = 0.8, and m h =  0.1) or equal ratios of the three biotypes ( m p  = 0.33, m m  = 0.33, and m h  = 0.33).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have now focused on biotype composition in different countries in Europe (Di Luca et al 2016, Gomes et al 2013a, Gomes et al 2009, Osório et al 2014, Rudolf et al 2013, Vogels et al 2016b, Zittra et al 2016. Thus far, most of these studies (including chapters 2 and 3) presented the average population composition, by combining data from mosquito collections of varying periods of time.…”
Section: Culex Pipiens Population Compositionmentioning
confidence: 99%